Linking gene expression to productivity to unravel long-and short-term responses of seagrasses exposed to CO2 in volcanic vents - Olive, Irene; Silva, João; Lauritano, Chiara; Costa, Monya M.; Ruocco, Miriam; Procaccini, Gabriele; Santos, Rui (Scientific Reports, 2017)
Ocean acidification is a major threat for marine life but seagrasses are expected to benefit from high CO2. In situ (long-term) and transplanted (short-term) plant incubations of the seagrass Cymodocea nodosa were performed near and away the influence of volcanic CO2 vents at Vulcano Island to test the hypothesis of beneficial effects of CO2 on plant productivity. We relate, for the first time, the expression of photosynthetic, antioxidant and metal detoxification-related genes to net plant productivity (NPP). Results revealed a consistent pattern between gene expression and productivity indicating water origin as the main source of variability. However, the hypothesised beneficial effect of high CO2 around vents was not supported. We observed a consistent long-and short-term pattern of gene downregulation and 2.5-fold NPP decrease in plants incubated in water from the vents and a generalized upregulation and NPP increase in plants from the vent site incubated with water from the Reference site. Contrastingly, NPP of specimens experimentally exposed to a CO2 range significantly correlated with CO2 availability. The down-regulation of metal-related genes in C. nodosa leaves exposed to water from the venting site suggests that other factors than heavy metals, may be at play at Vulcano confounding the CO2 effects. ESF COST Action [ES0906]; Portuguese Foundation for Science and Technology (FCT) [PTDC/MAR-EST/3687/2012]; Italian MIUR Flagship project RITMARE (NRP); FCT [UID/Multi/04326/2013, SFRH/BPD/71129/2010, SFRH/BD/64590/2009] info:eu-repo/semantics/publishedVersion